2023
DOI: 10.1007/s43450-023-00370-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Therapeutic Insights of Alpha-Lipoic Acid as a Potential Molecule for Disease Prevention

Abstract: Alpha-lipoic acid is an organic, sulfate-based compound produced by plants, humans, and animals. As a potent antioxidant and a natural dithiol compound, it performs a crucial role in mitochondrial bioenergetic reactions. A healthy human body, on the other hand, can synthesize enough α-lipoic acid to scavenge reactive oxygen species and increase endogenous antioxidants; however, the amount of α-lipoic acid inside the body decreases significantly with age, resulting in endothelial dysfunction. Molecular orbital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 130 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…On the other hand, it is widely used as part of dietary supplements and pharmaceutical dosage forms applied in medicine. α-Lipoic acid has multi-beneficial functions in the human organism [ 32 ], i.e.,…”
Section: Sulfur-containing Antioxidants and Their Action In Living Sy...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is widely used as part of dietary supplements and pharmaceutical dosage forms applied in medicine. α-Lipoic acid has multi-beneficial functions in the human organism [ 32 ], i.e.,…”
Section: Sulfur-containing Antioxidants and Their Action In Living Sy...mentioning
confidence: 99%
“…Biological aspects of sulfur-containing antioxidant actions, their metabolism, and implementation in diseases pathogenesis are discussed in detail in reviews [ 10 , 16 , 19 , 22 , 24 , 25 , 30 , 31 , 32 ].…”
Section: Sulfur-containing Antioxidants and Their Action In Living Sy...mentioning
confidence: 99%
“…13,14 Furthermore, it is worth noting that the carboxylic group, found in various naturally occurring antioxidants such as lipoic acid, plays a significant role in their activity. [17][18][19] Recent investigations have revealed that compounds derived from pentanoic acid demonstrate heightened neuroprotective capabilities, attributed to their ability to mitigate oxidative stress. 20 While earlier studies have extensively explored the one-electron oxidations of organosulfur compounds, both aliphatic and aromatic, there is a scarcity of reports on organoselenium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The body naturally produces alpha-lipoic acid (ALA), often referred to as thioctic acid (TA), which is necessary for the operation of certain oxidative metabolic enzymes [1,2]. Its main function is to use oxygen to turn blood sugar (glucose) into energy [3,4].…”
Section: Introductionmentioning
confidence: 99%